THE FRENCH POLITICAL INFLUENCE IN WEST AFRICA IN THE 21ST CENTURY: (INTER)DEPENDENT RELATIONS WITH THE FORMER METROPOLIS (CIPEEX, 2024)
THIS STUDY AIMS TO EXPLORE THE ENDURING INFLUENCE OF FRANCE IN WEST AFRICA DURING THE 21ST CENTURY, WITH A SPECIFIC FOCUS ON HOW THE COMPLEX RELATIONS THAT EXIST BEYOND ITS PREVIOUS COLONIES ARE MANIFESTED AND MAINTAINED IN THIS PORTION OF THE CONTINENT. THE METHODOLOGY UTILIZED IN THIS RESEARCH IS CENTERED ON BIBLIOGRAPHIC AND DOCUMENTARY ANALYSIS IN ORDER TO SHED LIGHT ON THE ACTIVE INTERVENTIONIST POLICY PRACTICE BY FRANCE AFTER THE FORMAL INDEPENDENCE OF THE NATIONS IN THIS REGION. DUE TO ITS DEEP HISTORICAL ROOTS, THE SO-CALLED 'FRANÇAFRIQUE' REMAINS A SIGNIFICANT STRATEGIC FOCAL POINT IN FRENCH FOREIGN POLICY. HOWEVER, GIVEN THE INCREASING INTEREST AND INFLUENCE OF OTHER NATIONS THROUGHOUT THIS CENTURY, THIS STATUS QUO IS GRADUALLY DIMINISHING, MAKING THIS CONNECTION AN ONGOING AND PERTINENT SUBJECT FOR DISCUSSION IN THE REALM OF INTERNATIONAL DIPLOMACY. THIS COMPLEX GEOPOLITICAL INTERPLAY EMPHASIZES THE IMPORTANCE OF ASSESSING THE SOVEREIGNTY OF THESE AFRICAN NATIONS IN THE CONTEXT OF FRANCE’S SPHERE OF INFLUENCE. AS PART OF THE COMPREHENSIVE ANALYSIS, THE STUDY EXAMINES THE UNDERLYING FACTORS SHAPING CONTEMPORARY FRANCO-WEST AFRICAN RELATIONS THROUGH THE REALIST PERSPECTIVE OF INTERNATIONAL RELATIONS. THIS APPROACH OFFERS VALUABLE INSIGHTS INTO THE POWER DYNAMICS, VESTED INTERESTS, AND MOTIVATING FORCES WITHIN THIS PERSISTENT GEOPOLITICAL NEXUS. IN ESSENCE, THE PAPER PROVIDES AN IN-DEPTH UNDERSTANDING OF FRANCE'S ONGOING IMPACT ON WEST AFRICA AND ITS CONSEQUENCES FOR REGIONAL SOVEREIGNTY, THUS ENRICHING THE BROADER DIALOGUE ON INTERNATIONAL DIPLOMACY AND GLOBAL POLITICS IN THE CONTEMPORARY ERA.